Primary squamous cell carcinoma of the breast: a rare entity, representation of two cases - Siripurapu, Yoshitha; Dev, Bhawna; Ramakrishnan, Ramya; Sundaram, Sandhya (International Surgery Journal, 2017)
The aim of this study was to diagnose primary squamous cell carcinoma of the breast with clinical, radiological, pathological correlation. We report two cases of primary squamous cell carcinoma of the breast. Both the patients presented with a palpable lump, with no family history of breast carcinoma. Post-operative histopathological diagnosis was squamous cell carcinoma with immunohistochemistry positive for p63 and negative for hormone receptors. Primary squamous cell carcinoma (SqCC) of the breast is a very rare tumor accounting for less than 0.1% of all invasive breast carcinomas. It is known to be a very aggressive which is a hormone receptor negative and is treatment refractory tumor with poor prognosis. In both our cases, a final diagnosis of SqCC was made after an extensive work up for primary or metastatic disease.